Analysis of Violations of the Indonesian Engineers Code of Ethics (PII) and Systemic Failures in the Hambalang P3son Project Case Study - Dicky Prima Alexander Manurung; Eka Daryanto; Syafiatun Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to examine in depth the implementation and violations of the engineering code of ethics in the Hambalang National Education, Training, and Sports School (P3SON) Project. The Hambalang Project, which experienced structural failure due to neglect of geotechnical engineering principles and political collusion, is used as a case study of systemic failure. The analysis focuses on violations of the Sapta Dharma of the Indonesian Engineers Association (PII) and the evaluation of professional responsibility based on ethical theories (Deontology, Teleology, and Virtue Ethics). The analysis results indicate that ethical violations, especially conflicts of interest and systemic corruption, are the main causes that trigger technical violations (ignoring the risks of expansive clay soil). The identified fundamental violations are Sapta Dharma Point 1 (Prioritizing Public Safety), Point 2 (Working According to Competence), and Point 4 (Avoiding Conflicts of Interest). Recommendations proposed include systemic solutions such as the separation of critical contracts and mandatory independent design validation (peer review) to strengthen the culture of engineering ethics.